1963
DOI: 10.1021/jo01046a538
|View full text |Cite
|
Sign up to set email alerts
|

The Reduction of Esters with Sodium Borohydride1

Abstract: anol (6 ml.) added to dissolve the aniline. The yield of amine was 1.35 g. (91%). Benzamide had m.p. 62-65°, lit.13 63-65°.N-Benzylaniline.-The method was similar to the previous with aniline and benzaldehyde (5 ml.), and ethanol (20 ml.).The yield was 1.67 g" (83%), m.p. 36-37.2°, lit.14 37-38°.N-Ethylpiperidine.-The method was similar to the previous with piperidine, 1.0 ml. (10.1 mmoles), and acetaldehyde (10 ml.). The borohydride was added over 30 min.; half of the acetaldehyde was added at the beginning, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0
1

Year Published

1965
1965
2010
2010

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(48 citation statements)
references
References 1 publication
1
46
0
1
Order By: Relevance
“…Although not common, such a reduction of esters by sodium borohydride does have precedent. 5 In our hands the transformation of 6 to 7 went very smoothly and in good yield (Scheme 1).…”
Section: Discussionmentioning
confidence: 58%
“…Although not common, such a reduction of esters by sodium borohydride does have precedent. 5 In our hands the transformation of 6 to 7 went very smoothly and in good yield (Scheme 1).…”
Section: Discussionmentioning
confidence: 58%
“…esters, nitro, nitriles, etc., remain unaffected [110]. Although it has been reported that some aliphatic and aromatic esters have been reduced with a large excess of sodium or other metal borohydrides [1112], often in higher boiling solvents [13] and in combination with various additives [1415] including at a cationic micellar surface [16], selective reduction of the keto group in oxoesters has been accomplished using potassium borohydride in refluxing ethanol [17] where the product distribution critically depends on the relative proportions of substrate and reagent. Despite the occurrence of several recent reports of borohydride-mediated reduction of the ester moiety in α-oxo- [1819] and β-oxoesters [20], sodium borohydride in various alcoholic solvents, often in the presence of additives [21], has been judiciously utilized [22] for the chemoselective reduction of the oxo-group, occasionally with subsequent transesterification and the formation of the alkoxy-modified β-hydroxyesters.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Although this reducing agent has been constantly used for reduction of aldehydes, ketones and other important functional groups, it is not common to use NaBH 4 itself for reduction of esters. [4][5][6] Due to this low reactivity towards esters, additives which enhance the activity of NaBH 4 have been reported. 7 For example, addition of iodine to NaBH 4 in THF provides H 3 B-THF, which is useful for hydroborations, reduction of esters and various others functional groups.…”
Section: Introductionmentioning
confidence: 99%